ANALISIS PROBLEMATIKA DAN STRATEGI DALAM PEMBELAJARAN MEMBACA PERMULAAN DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Aulia Dila Pratiwi (Jurnal Binagogik, 2026)
This study aims to analyze various issues and strategies in early reading learning in elementary schools based on the results of a Systematic Literature Review (SLR) of 25 journal articles. This study was motivated by the fact that early reading skills are the main foundation for students' literacy development, but its implementation still faces various obstacles, ranging from pedagogical, linguistic, and learning environment aspects. This study uses a Systematic Literature Review (SLR) approach with the PRISMA model, involving the selection, categorization, and synthesis of data from various research results from 2015 to 2025. The results of the study show that the main problems in early reading learning include low student motivation and interest in learning, limited contextual learning media, conventional teaching methods, and low teacher understanding of the characteristics of early grade students. Meanwhile, effective strategies include the application of phonics and synthetic analytical structural (SAS) methods, the use of visual media such as letter and syllable cards, a multisensory approach, and collaboration between teachers and parents. Effective early reading learning requires teachers to play an active role as facilitators who understand the individual needs of students and create a pleasant learning atmosphere. The findings of this study are expected to contribute to the development of policies, learning strategies, and innovations in educational media that are more adaptive and oriented towards the basic literacy of primary school children.